A synthesis on the impact of non-native conifer plantations on ant and beetle diversity in norh-western Patagonia - Corley, Juan Carlos; Dimarco, Romina Daniela; Fischbein, Deborah; Lantschner, Maria Victoria; Martinez Von Ellrich, Andres; Masciocchi, Maite; Mattiacci, Analia; Paritsis, Juan; Villacide, Jose Maria (2018)
Softwood forestry with non-native tree species is increasing worldwide and especially in many developing countries of the Southern Hemisphere. Tree plantations are beneficial in environmental and socioeconomic aspects, but at the same time there are recognised costs associated with afforestation. Our aim was to revise the existing information on the impact of exotic conifer plantations in north-western Patagonia on insect biodiversity. A total of five studies were selected and, in these, not every insect group responded in a similar manner to the habitat replacement. There was a tendency towards a reduction in abundance and species richness of several insects inside pine plantations. This change in abundance and richness was especially evident for ant assemblages and when pine plantations were dense. Beetle assemblages, in turn, showed diverse responses to the replacement of native vegetation with forests depending on the native habitat matrix. Our findings confirm that practices that reduce tree density (via thinning or during plantation) should be recommended to minimise their impact on insect biodiversity in north-western Patagonia. The consistent behaviour of ant assemblages, coupled with their abundance, ease to sample and unambiguous taxonomy make them reliable candidates for long-term monitoring of the impact conifer forestation in north-western Patagonia, as well as probably in other regions of the world in which non-native pines replace natural environments.